Planned vaginal delivery or planned caesarean delivery in women with extreme obesity. - Homer, C; Kurinczuk, J; Spark, P; Brocklehurst, P; Knight, M (2011)
OBJECTIVE: To compare the outcomes of planned vaginal versus planned caesarean delivery in a cohort of extremely obese women (body mass index ≥ 50 kg/m(2)). DESIGN: A national cohort study using the UK Obstetric Surveillance System (UKOSS). SETTING: All hospitals with consultant-led maternity units in the UK. POPULATION: Five hundred and ninety-one extremely obese women delivering in the UK between September 2007 and August 2008. METHODS: Prospective cohort identification through UKOSS routine monthly mailings. MAIN OUTCOME MEASURES: Anaesthetic, postnatal and neonatal complication rates. RESULTS: After adjustment, there were no significant differences in anaesthetic, postnatal or neonatal complications between women with planned vaginal delivery and planned caesarean delivery, with the exception of shoulder dystocia (3% versus 0%, P = 0.019). There were no significant differences in any outcomes in the subgroup of women who had no identified medical or antenatal complications. CONCLUSIONS: This study does not provide evidence to support a routine policy of caesarean delivery for extremely obese women on the basis of concern about higher rates of delivery complications, but does support a policy of individualised decision-making on the mode of delivery based on a thorough assessment of potential risk factors for poor delivery outcomes.